Protein kinase structure, function and regulation - Taylor, Susan (Henry Stewart Talks, 2010)
Overview of protein kinase structure and function using PKA as a prototype for this enzyme superfamily, What we have learned from the overall structural kinome, Comparison of many protein kinases, Eukaryotic protein kinase regulation, Elucidation of general rules of architecture, Illustration of how PKA is regulated by cAMP and how it is localized to specific macromolecular complexes through scaffold proteins